Remineralizador a base de pó de basalto no cultivo de couve-manteiga - Nascimento, Viviane Rocha Ramos (2023)
The municipality of Uberlândia, in the Triângulo Mineiro region, has a large reserve of rock of basaltic origin, which, after being processed and transformed into rock powder, can be used as a soil remineralizer and can be used as a complement to mineral fertilization, which meets the country's need to develop new technologies and reduce external dependence on the main fertilizers used in national agricultural production. This study aimed to evaluate different doses of basalt powder as a complementary source of mineral fertilizer and relate it to the nutritional status and agronomic attributes of butter cabbage. The study was conducted in a completely randomized design, evaluating six doses of basalt powder: T1 = 0.0 (without basalt powder); T2 = 2.0; T3 = 4.0; T4 = 6.0; T5 = 8.0 and T6 = 10.0 t ha-1 of basalt powder. In all treatments, mineral fertilizer was applied, formulated NPK at a dose of 111 g m-2 + organic fertilizer Forte C at a dose of 1000 g m-2), with four replications. Three leaf harvests were carried out at approximate intervals of 30 days and the nutritional status of the plant at the time of harvest, the number of leaves per plant (NP), vertical length (VL) and horizontal length (HL), fresh mass (FM) and dry mass (DM) of the butter cabbage leaves were assessed. It was observed that the use of basalt powder as a complementary source of mineral fertilizer in the cultivation of butter cabbage provided an increase in VL, HL, FM and DM of the leaves, reaching a maximum value of 33.11, 23.40, 776.22 and 120.97 cm, up to the maximum applied dose of 6 t ha-1, respectively. The leaf content of N, K, Ca, S and Cu increased, while that of P, Mg, Mn, Zn, B, Mo decreased as the doses of basalt powder increased. The accumulation of P, Mg, Mn, Zn, B, Cu in the plant decreased as the doses of basalt powder increased.